Mindfulness Training for People With Dementia and Their Caregivers: Rationale, Current Research, and Future Directions - Berk, Lotte; Warmenhoven, Franca; van Os, Jim; van Boxtel, Martin (Frontiers in Psychology, 2018)
The world population is aging and the prevalence of dementia is increasing. By 2050, those aged 60 years and older are expected to make up a quarter of the population. With that, the number of people with dementia is increasing. Unfortunately, there is no cure for dementia. The progression of symptoms with no hope of improvement is difficult to cope with, both for patients and their caregivers. New and evidence-based strategies are needed to support the well-being of both caregiver and patient. Mindfulness training is a body-mind intervention that has shown to improve psychological well-being in a variety of mental health conditions. Mindfulness, a nonjudgmental attention to one’s experience in the present moment, is a skill that can be developed with a standard 8-week training. Research has shown preliminary but promising results for mindfulness-based interventions to benefit people with dementia and caregivers. The aim of this review is (a) to provide a rationale for the application of mindfulness in the context of dementia care by giving an overview of studies on mindfulness for people with dementia and/or their caregivers and (b) to provide suggestions for future projects on mindfulness in the context of dementia and to give recommendations for future research.